Effect of buffers and supplemental potassium in diets of early-weaned calves - K.J. Jordan; J.L. Morrill; P.G. Reddy; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 1986)
Potassium chloride added to the prestarter and/or potassium bicarbonate added to the starter fed to early weaned calves helped maintain normal blood alkalinity and normal levels of blood gases, and resulted in a trend toward increased feed consumption. Potassium bicarbonate added to the starter tended to improve weight gains.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Potassium; Gain; Feed consumption